The Application of Non-Destructive Geophysical Measurements for Mapping and Surveying the Hillforts in the Czech Republic - Křivánek, Roman (Archaeologia Lituana, 2018)
[full article, abstract in English; abstract in Lithuanian] The Czech landscape and its archaeological resources include the most varied types of prehistoric or early medieval hillforts. These fortified sites are found across a variety of different locations and possess different functions and dimensions (very often in units of hectares, unlike the later medieval strongholds, characterized by the dimensions of tenths of hectares of fortified areas). Due to this large area, the hillforts were verified using mainly small-scale archaeological investigations. Many other hillforts are also known to exist without any archaeological trenching, research or exact dating. A combination of various remote sensing techniques and non-destructive methods seems to be, in the last two decades, a fast and low-priced way to acquire new spatial information about these fortified sites. Geophysical measurements of hillforts and different me- thods were under all circumstances limited by various field conditions and the performance of used equipment. But some of the geophysical methods now offer new surveys of large areas of hillforts or nearly complete fortified sites. Seven chosen examples of various geophysical methods and techniques in this paper should illustrate the different possibilities of modern prospection and non-destructive mapping of hillforts. Their results could be used in archaeology, heritage care of intangible archaeological monuments or on different occasions for particular kinds of conservation, new protection or systematic study of hillforts.